On the Solution of Wave-Schrodinger Equation (Global Journal of Science Frontier Research, 2019)
In this paper, we are finding solution of fraction Wave-Schrodinger equation by Laplace transform in sense of Caputo fractional derivative. It was found that the fundamental solution of the equation related to Wright function.
Keywords: dirac delta distribution; laplacian operator; wright function